Cloning of a Tobacco Apoplasmic Invertase Inhibitor : Proof of Function of the Recombinant Protein and Expression Analysis during Plant Development - Greiner, Steffen (American Society of Plant Physiologists, 1998)
Higher plants express several isoforms of vacuolar and cell wall invertases (CWI), some of which are inactivated by inhibitory proteins at certain stages of plant development. We have purified an apoplasmic inhibitor (INH) of tobacco (Nicotiana tabacum) CWI to homogeneity. Based on sequences from tryptic fragments, we have isolated a full-length INH-encoding cDNA clone (Nt-inh1) via a reverse transcriptase-polymerase chain reaction. Southern-blot analysis revealed that INH is encoded by a single- or low-copy gene. Comparison with expressed sequence tag clones from Arabidopsis thaliana and Citrus unshiu indicated the presence of Nt-inh1-related proteins in other plants. The recombinant Nt-inh1-encoded protein inhibits CWI from tobacco and Chenopodium rubrum suspension-cultured cells and vacuolar invertase from tomato (Lycopersicon esculentum) fruit, whereas yeast invertase is not affected. However, only in the homologous system is the inhibition modulated by the concentration of Suc as previously shown for INH isolated from tobacco cells. Highly specific binding of INH to CWI could be shown by affinity chromatography of a total cell wall protein fraction on immobilized recombinant Nt-inh1 protein. RNA-blot analysis of relative transcript ratios for Nt-inh1 and CWI in different parts of adult tobacco plants revealed that the expression of both proteins is not always coordinate.